Empirical evidence for integration and disintegration of maritime shipping, port and logistics activities - Antoine Frémont (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2008)
In 50 years, containerisation has become the backbone of globalisation. That it has done so can be attributed to the beneficial interaction of three broad types of factor: technical, economic and organisational. In the beginning, containerisation was nothing more than a simple technical innovation. However, as an intermodal tool, the container paved the way for new and long-term organisational models in the transport sector. These organisational factors challenged transport actors, who had to redefine the demarcation lines between their respective businesses in order to bring reliable door-to-door transport chains with a global reach into operation. The opportunities that containerisation offered would have remained a dead letter had they not coincided with the deep upheavals in economic factors since the 1970s. The very strong growth in international trade in manufactured products, systematically higher than growth in international trade overall - itself higher than GDP growth - marks a deeper division in international labour, which was made possible only through the support of a strong transport system.
Keywords: 330